2020
DOI: 10.21203/rs.3.rs-104566/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut Microbiome of the Amazon Master of the Grasses Harbors Unprecedented Enzymatic Strategies for Plant Glycans Breakdown

Abstract: BackgroundPlant biomass is a promising feedstock to replace fossil-based products including fuels, chemicals and materials. However, the high resistance of plant biomass to either physicochemical or biological deconstruction has been hampering its broad industrial utilization and, consequently, the transition to a sustainable bioeconomy. The gut system from herbivores are formidable bioreactors in nature for lignocellulose breakdown and the diverse ecological niches where herbivores are found have led to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…In captive sifakas (Propithecus coquereli), supplementing standard diets with diverse foliage blends versus with single plant species, was associated with greater concentrations of short-chain fatty acids (SCFAs) in the gut (123). At a larger scale across wild mammals, from rodents to carnivores and primates, several studies have found associations between specific microbial functions and diet type (herbivore, omnivore, piscivore, carnivore) (35,124,125).…”
Section: Host Diet Is Correlated With Gut Microbiome Variationmentioning
confidence: 99%
“…In captive sifakas (Propithecus coquereli), supplementing standard diets with diverse foliage blends versus with single plant species, was associated with greater concentrations of short-chain fatty acids (SCFAs) in the gut (123). At a larger scale across wild mammals, from rodents to carnivores and primates, several studies have found associations between specific microbial functions and diet type (herbivore, omnivore, piscivore, carnivore) (35,124,125).…”
Section: Host Diet Is Correlated With Gut Microbiome Variationmentioning
confidence: 99%